2004
DOI: 10.1063/1.1697627
|View full text |Cite
|
Sign up to set email alerts
|

A distributed charge storage with GeO2 nanodots

Abstract: In this study, a distributed charge storage with GeO2 nanodots is demonstrated. The mean size and aerial density of the nanodots embedded in SiO2 are estimated to be about 5.5 nm and 4.3×1011 cm−2, respectively. The composition of the dots is also confirmed to be GeO2 by x-ray absorption near-edge structure analyses. A significant memory effect is observed through the electrical measurements. Under the low voltage operation of 5 V, the memory window is estimated to ∼0.45 V. Also, a physical model is proposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…As this happens, nucleation and growth of the hexagonal GeO 2 phase start. The hexagonal GeO 2 phase is indeed observed using SEM and XRD after the LPD process proceeds for 2 h. We have studied the morphology evolution of hexagonal GeO 2 phases in the acid-induced LPD process [11]. It is found that a hexagonal prism with two hexagonal pyramids at both ends will slowly develop a truncated cube-like shape, and then a cube-like shape [22].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As this happens, nucleation and growth of the hexagonal GeO 2 phase start. The hexagonal GeO 2 phase is indeed observed using SEM and XRD after the LPD process proceeds for 2 h. We have studied the morphology evolution of hexagonal GeO 2 phases in the acid-induced LPD process [11]. It is found that a hexagonal prism with two hexagonal pyramids at both ends will slowly develop a truncated cube-like shape, and then a cube-like shape [22].…”
Section: Resultsmentioning
confidence: 94%
“…Recently much attention has been given to GeO 2 due to its potential applications in light emitting devices [1][2], infrared waveguide [3][4][5], catalyst [6,7], biomedicine [7,8], vacuum technique and piezoelectric devices [9][10][11]. Melting, sputtering deposition, chemical vapor deposition, flame hydrolysis, electrospinning, laser ablation, physical evaporation, thermal oxidation, reversed micelles and sol-gel method have been used to prepare the GeO 2 materials [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have focused on the fabrication on Si and Ge nanocrystals in metal-oxidesemiconductor (MOS) structure [12][13][14][15][16][17][18][19][20]. In addition, atomicforce-microscopy (AFM) was utilized to inject charges in the nanocrystals [21][22][23].…”
Section: Nanocrystals Structurementioning
confidence: 99%
“…Although Ge-incorporated HfON has been proposed to enhance the charge-trapping capability for nonvolatile memory [20], most Ge-related materials for charge-trapping applications are pertinent to nanocrystal-based trapping media. Nanocrystal-based memory devices indeed exhibit prominent electrical performance [21]- [26]; however, controlling the size and uniformity of nanocrystals is still a challenge that needs to be overcome. Ge 3 N 4 , which was formed by ammonia (NH 3 ) plasma nitridation of an amorphous Ge film in this study, has demonstrated great potential for advanced flash memory application in terms of a large memory window, highspeed operation as well as robust endurance and satisfactory retention.…”
Section: Introductionmentioning
confidence: 99%